2008
DOI: 10.3892/or.19.5.1231
|View full text |Cite
|
Sign up to set email alerts
|

Genistein differentially modulates androgen-responsive gene expression and activates JNK in LNCaP cells

Abstract: Genistein, the predominant isoflavone in soy, may be chemopreventive in prostate cancer (CaP). It downregulates the prostate-specific antigen (PSA) and androgen receptor (AR) in androgen responsive cells. However, the extent of the down-regulation and whether genistein has a general effect on all androgen responsive genes (ARGs) are unclear. We investigated the ability of genistein to modulate ARG expression by the synthetic androgen R1881 in LNCaP cells. Given that there is important crosstalk between AR and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…In models pertaining to PCA, genistein inhibits receptor tyrosine kinases, nuclear factor kappa B (NF-kB) and vitamin D-24-hydroxylase thus induces apoptosis (10, 13) and enhances calcitriol action to inhibit proliferation of PCA cells (29, 37). Genistein activates tumor suppressor genes (12, 15), inhibits metastasis (13), modulates androgen-responsive gene expression (14), and down-regulates prostate-specific antigen (PSA) (9) and the androgen receptor (7). …”
Section: Discussionmentioning
confidence: 99%
“…In models pertaining to PCA, genistein inhibits receptor tyrosine kinases, nuclear factor kappa B (NF-kB) and vitamin D-24-hydroxylase thus induces apoptosis (10, 13) and enhances calcitriol action to inhibit proliferation of PCA cells (29, 37). Genistein activates tumor suppressor genes (12, 15), inhibits metastasis (13), modulates androgen-responsive gene expression (14), and down-regulates prostate-specific antigen (PSA) (9) and the androgen receptor (7). …”
Section: Discussionmentioning
confidence: 99%
“…These results provide evidence to support the inhibitory effect of genistein on AR expression and/or transcriptional activity. However, some in vitro studies demonstrated stimulatory effects of isoflavones particularly genistein at certain low doses [190192]. The cause of these controversial results is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Although in a number of in vitro studies genistein downregulated AR transcription and PSA protein expression in PCa cells and inhibited their growth [24,26,27], stimulatory effects have been also reported [4547]. However, most of these studies have some methodological limitations.…”
Section: Introductionmentioning
confidence: 99%